Clinical characteristics and frailty status in heart failure with preserved vs. reduced ejection fraction - Tomoyuki Hamada; Toru Kubo; Kazuya Kawai; Yoko Nakaoka; Toshikazu Yabe; Takashi Furuno; Eisuke Yamada; Hiroaki Kitaoka; Kochi YOSACOI study (ESC Heart Failure, 2022)
Abstract Aims The aim of this study was to elucidate the clinical characteristics, including frailty status, of patients with heart failure with preserved ejection fraction (HFpEF) in comparison with those in patients with heart failure with reduced ejection fraction (HFrEF) in a super‐aged region of Japan. Methods and results Of the 1061 Japanese patients enrolled in the Kochi YOSACOI study, a multicentre registry, we divided 645 patients (median age of 81 years [interquartile range, 72–87 years]; women, 49.1%) into two groups, HFpEF patients (61.2%) and HFrEF patients (38.8%). Physical frailty was diagnosed on the basis of the Japanese version of Cardiovascular Health (J‐CHS) Study criteria. Patients for whom left ventricular ejection fraction data were not available (n = 19), patients with heart failure with mildly reduced ejection fraction (n = 172), and patients who were not assessed by the J‐CHS criteria (n = 225) were excluded. The median ages of the HFpEF and HFrEF patients were 84 and 76 years, respectively. The proportion of patients with HFpEF gradually increased with advance of age. The proportion of patients with three or more comorbidities was larger in HFpEF patients than in HFrEF patients (77.9% vs. 65.6%, P = 0.003). Handgrip strength was significantly lower in HFpEF patients than in HFrEF patients for both men (P < 0.001) and women (P = 0.041). Comfortable 5 m walking speed was significantly slower in HFpEF patients than in HFrEF patients (P < 0.001). The proportions of patients with physical frailty were 55.2% in HFpEF patients and 46.8% in HFrEF patients, and the proportion was significantly higher in HFpEF patients (P = 0.043). In multivariate analysis, physical frailty was associated with advanced age [odds ratio (OR), 1.030; 95% confidence interval (CI), 1.010–1.050; P = 0.023] and low albumin level (OR, 0.334; 95% CI, 0.192–0.582; P < 0.001) in HFpEF patients, and physical frailty was associated with women (OR, 2.150; 95% CI, 1.030–4.500; P = 0.042) and anaemia (OR, 2.840; 95% CI, 1.300–6.230; P = 0.003) in HFrEF patients. Conclusions In a super‐aged population of HF patients in Japan, HFpEF patients are more likely to be frail/have a high frailty status compared with HFrEF patients. The results suggested that physical frailty is associated with extracardiac factors in both HFpEF patients and HFrEF patients.